Method for producing artificial panels provided with flame retardants

By using a flame retardant composition of a mixture of phosphate and silane during the manufacturing process of the OSB plate, the problem of poor flame retardant distribution and fixation is solved, and a higher flame retardant retention rate and lower production costs are achieved.

CN119836342APending Publication Date: 2025-04-15SWISS KRONO TEC AG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380062809.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-24
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When manufacturing flame retardant OSB boards, it is difficult to evenly distribute and fix the flame retardant, resulting in loss in the process, increasing cost and process complexity.

Method used

Using a flame retardant composition containing a mixture of phosphate and silane, the adhesion of the phosphate is improved by reacting silane with the surface of wood particles, thereby reducing the wear and drop of the flame retardant.

Benefits of technology

Improves the retention rate of flame retardant on OSB boards, reduces the required amount and production costs, and simplifies the process flow.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for producing artificial panels provided with flame retardants, in which during the production process at least one flame retardant in the form of a suspension is applied to wood particles, the flame retardant suspension comprising a mixture of at least one phosphate and / or sulfate, consisting of at least one compound of general formula (I) R1 aSiX (4-a), wherein X is an alkoxy group, and R1 is an organic residue selected from alkyl, cycloalkyl or phenyl, and a = 1, 2, 3, in particular 1 or 2; at least one compound of general formula (II) SiX4, wherein X is an alkoxy group; and at least one compound of general formula (III) R2SiX3 in which X is an alkoxy group and R2 is an organic residue selected from the group consisting of C1-C10 alkyl groups which can be broken by-O-or-NH-, and in which R2 has at least one functional group Q1 selected from the group consisting of methacrylic groups, methacryloyloxy groups, vinyl groups and epoxy groups.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for producing a wood-based panel provided with a flame retardant and to a wood-based panel comprising the flame retardant. Background Art

[0002] In recent years, serious fires have repeatedly occurred in buildings, sometimes causing a large number of casualties. This has led to the strengthening of legal provisions on fire protection. However, in parallel, certain flame retardants have also been banned or their use has been strictly regulated due to ecological or health considerations (such as boron salts). In addition to the resulting enhanced requirements for the flammability / combustibility of products in certain applications, the demand for non-flammable products can also be stipulated in many applications where fire protection is not important. This also applies to artificial wood, which is used in structural areas for walls, floors or ceilings (prefabricated house construction) or in decorative areas for laminate floors, furniture, panels, etc. Here, OSB (Oriented Strand Board), plywood and chipboard are used in structural areas, and MDF / HDF (medium density fiberboard / fiberboard with increased bulk density) and chipboard are used in decorative areas.

[0003] In the production of inflammable artificial wood, inorganic salts are usually used. These are almost exclusively sulfates, phosphates and / or polyphosphates as ammonium salts. This is because these salts provide particularly good results with regard to inflammability. These salts must be used in solutions with relatively high concentrations, since otherwise additional problems arise due to the water contained in the salt suspension used, so that the water must be removed from the process.

[0004] While it is relatively simple to introduce flame retardants (FSM) into the wood matrix when making flame retardant wood chips or fiberboards, there are problems when adding them to OSB wood chips. Wood chips are the coarse wood chips used to make OSB.

[0005] However, OSB, which originally emerged as a by-product of the veneer and plywood industry, is increasingly being used in wooden and prefabricated house construction, since OSB is lightweight and still meets the static requirements imposed on building panels. OSB is therefore used as building panels and wall or roof linings or also in the floor sector.

[0006] The production of OSB takes place in a multi-stage process, in which wood chips or shavings are firstly stripped from debarked round timber, preferably softwood, in the longitudinal direction by means of rotating knives. In the subsequent drying process, the natural moisture content of the shavings is reduced at high temperatures. The degree of moisture content of the shavings can vary depending on the adhesive used, wherein the moisture content should be significantly shifted to less than 10% in order to avoid cracks caused by excessive steam pressure in the board during the subsequent pressing. Depending on the adhesive, it can be more advantageous to wet the shavings, which may be wet, or to wet the shavings, which may be dry.

[0007] After the wood chips have been dried, they are introduced into a glue application plant, where glue or adhesive is applied to the wood chips in a finely distributed manner. For the glue application, PMDI (polymeric diphenylmethane diisocyanate) or MUPF glue (melamine-urea-phenol-formaldehyde) is mainly used. The glue can also be used in a mixed form for OSB. The glue is used because, as mentioned above, OSB is often used for structural applications. A moisture-resistant or moisture-proof glue must be used here.

[0008] After the gluing, the gluing chips are spread in a spreading device alternately along the production direction and transversely to the production direction, so that the chips are arranged crosswise in at least three layers (lower cover layer - middle layer - upper cover layer). The spreading direction of the lower cover layer and the upper cover layer is the same here, but it is different from the spreading direction of the middle layer. The chips used in the cover layer and the middle layer are also different from each other. Therefore, the chips used in the cover layer are planar, while the chips used in the middle layer are less planar and even sawdust-like. Usually, two material strips are moved during the production of OSB: one with planar chips for the subsequent cover layer and one with "sawdust" for the middle layer. Correspondingly, the chips in the middle layer can be inferior in quality, because the bending strength is basically generated by the cover layer. Therefore, fine particles generated during chipping can also be used in the middle layer of the OSB board. After spreading the chips, they are continuously pressed under high pressure and high temperature, for example 200° C. to 250° C.

[0009] The OSB wood chips used in the production have a surface that makes it difficult for an aqueous solution of the flame retardant to penetrate. This results in the flame retardant being present on the wood chips essentially as a powder, unbound, after the water evaporates. Since the wood chips rub against each other until they are spread by the transport equipment, part of the flame retardant is ground off by the wood chips. The flame retardant is then lost in the process or is found again in the area of ​​the OSB where it has no effect on the flammability. This results in the need to increase the dosage, which causes additional costs. This is evident, for example, in the case where the FSM is only placed in the cover layer, but is later also found again in the product of the middle layer. In addition, an increased amount of flame retardant must be taken into account in the case of more glue, since the flame retardant interferes with the glue application.

[0010] Furthermore, the production of flame-retardant wood-based panels is generally complex, and OSB in particular is very complex, since approximately 20% by weight of flame retardant must be added to the wood of the panel. It should be taken into account that a non-negligible amount of the product must be discarded at the beginning and end of production, since the required amount of flame retardant is not or no longer present in the wood chips. This also results in increased costs and inflexible processes, since the largest possible amount of non-flammable panels must always be produced in order to keep losses in terms of production to a minimum.

[0011] Furthermore, solutions of flame retardants usually have about 50% by weight of flame retardant. Higher concentrations are still only possible by heating the solution, which is technically not feasible on many systems. Due to the amount of water introduced into the system, the dosage is also limited, since too high an amount of water causes too high a vapor pressure in the board and thus cracks. This of course also causes the highly concentrated flame retardant to be distributed more poorly on the wood chips than in a solution with a lower concentration.

[0012] Another problem is that, in order to increase the production speed, steam injection facilities are now installed before the flat presses. The hot steam ensures that the wood chip cake is preheated so that the temperature required for hardening the glue used, such as PMDI glue, is reached more quickly. The steam applied to the wood chips at high pressure will of course also wash some of the flame retardant out of the wood chips.

[0013] This results in disadvantages, in particular higher costs, greater losses and inflexible processes. Summary of the invention

[0014] The technical object on which the present invention is based is therefore to solve the above-mentioned problems. If feasible, this should be achieved without major changes to the process. The solution should also not create any other problems, for example by adding key ingredients or solvents. The solution that can be applied should also be compatible with the flame retardants used.

[0015] This object is achieved according to the invention by a method for producing a wood-based panel provided with a flame retardant having the features of claim 1 .

[0016] Accordingly, a method for producing a wood-based panel from wood particles is provided, wherein during the production process at least one flame retardant is applied to the wood particles in the form of a suspension, in particular an aqueous suspension, wherein the flame retardant suspension comprises the following components:

[0017] - at least one phosphate and / or sulfate, and

[0018] - A mixture consisting of:

[0019] - at least one compound of formula (I)

[0020] R1 a SiX (4-a) (I)

[0021] in

[0022] -X is an alkoxy group, and

[0023] -R 1 is an organic residue selected from: alkyl, cycloalkyl or phenyl, and

[0024] - a = 1, 2, 3, especially 1 or 2,

[0025] - at least one compound of formula (II)

[0026] SiX4(II),

[0027] wherein X is an alkoxy group, and

[0028] - at least one compound of formula (III)

[0029] R 2 b SiX3(III),

[0030] in

[0031] -X is an alkoxy group, and

[0032] -R 2 is an organic residue selected from: a C1-C10 alkyl group, the C1-C10 alkyl group being capable of being disconnected by -O- or -NH-, and

[0033] -R 2 having at least one functional group Q1 selected from the group consisting of a methacrylic acid group, a methacryloyloxy group, a vinyl group and an epoxy group,

[0034] - b=1, 2, 3, especially 1 or 2.

[0035] Therefore, a composition consisting of at least one phosphate and a silane mixture is provided for use in wood-based panels, wherein the silane or silane mixture used is used as a fixing agent for the phosphate or sulfate on the wood particles for the wood-based panels; that is, the fixing agent for the flame retardant is introduced onto the wood particles by means of the silane. This is to avoid or reduce the wear / dropping of the flame retardant after application to the wood particles, such as wood chips or sawdust, until the wood particles are pressed into wood-based panels. For this purpose, a silane mixture consisting of three different silanes is added to the flame retardant before being applied to the wood particles. This can be done in a storage tank or before the flame retardant is applied to the wood particles.

[0036] Silanes react with flame retardants on the one hand, and react with the surface of wood particles on the other hand. Silane compounds improve the adhesion of phosphates on the wood surface of wood particles through their reactivity with wood surfaces. Silane compounds of formula (I) are bound to flame retardants via organic residues. Silane compounds of formula (II) are used to construct SiO2 networks via condensation of OH groups. The alkyl groups of the silane compounds of formula (I), such as methyl groups, cause "loosening" of the three-dimensional SiO2 network formed by condensation. A more flexible network structure that is not too brittle is constructed. Silane compounds of formula (III) have at least one functional group, such as an isocyanate group or a glycidyl group, for chemical bonding to the free OH groups of cellulose on the surface of wood particles.

[0037] The use of the composition of the present invention as a flame retardant provides different advantages. Therefore, the flame retardant can be targeted more precisely, so that the amount of flame retardant required can be reduced, thereby reducing the cost of the flame retardant. Better material utilization can also be achieved.

[0038] The (hydrolyzable) residue X of the silane compound of formula (I) to (III) is advantageously selected from: C 1-6 - alkoxy, in particular methoxy, ethoxy, n-propoxy or isopropoxy and butoxy. Particular preference is given to methoxy and ethoxy.

[0039] The organic residue R of the compound of general formula (I) 1 Preferably selected from: C1-C10 alkyl, preferably C1-C8 alkyl, especially preferably methyl, ethyl, propyl, pentyl, hexyl, heptyl, octyl. The term "cycloalkyl" includes cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl and cycloheptyl.

[0040] The compounds of general formula (I) may in particular comprise one of the following formulae: 1 SiX3 or R 1 2SiX2, where R 1 As C1-C10 alkyl, methyl, ethyl, propyl, pentyl, hexyl, heptyl, octyl are preferred, and as alkoxy, X is especially methoxy, ethoxy, n-propoxy or isopropoxy.

[0041] In one variant of the composition of the invention, according to R 1 a SiX (4-a) , especially R 1 The compound of general formula (I) of SiX3 can be selected from methyltriethoxysilane, phenyltriethoxysilane, dimethyldiethoxysilane, and octyltrimethoxysilane.

[0042] In a particularly preferred variant of the present composition, the compound of the general formula (II) SiX4 comprises methoxy, ethoxy, n-propoxy or isopropoxy and butoxy as X. Particularly preferred are the compounds tetramethoxysilane and tetraethoxysilane as compounds of the general formula (II).

[0043] The organic R of the compound of formula (III) 2 Preferably, it is selected from the group consisting of: methyl, ethyl, propyl, pentyl, hexyl, heptyl, octyl, which can be cleaved via -O- or -NH-.

[0044] In one embodiment of the composition of the present invention, at least one functional group Q of the compound of formula (III) 1 is selected from the group consisting of epoxy, methacryloyloxy, amino and vinyl. 1 is a glycidyl group. Functional group Q 1 Advantageously, they have residues with double bonds or epoxy groups which can be activated and polymerized by means of UV radiation.

[0045] The functional groups via which crosslinking with the wood surface of the wood particles can occur include in particular polymerizable and / or polycondensable groups, wherein a polymerization reaction is also understood to be a polyaddition reaction. The functional groups are preferably selected such that organic crosslinking can be formed between the phosphate / sulfate as flame retardant and the wood surface via an optionally catalyzed polymerization and / or condensation reaction.

[0046] In a particularly preferred variant of the composition according to the invention, the compound of the general formula (III) comprises methoxy, ethoxy, n-propoxy or isopropoxy and butoxy as X, preferably methoxy and ethoxy.

[0047] Particularly preferred are compounds glycidylpropyltrimethoxysilane and glycidylpropyltrimethoxysilane as the compound of the general formula (III).

[0048] According to one variant, the composition comprises a silane mixture in which the first compound of formula (I) corresponds to R 1 a SiX (4-a) , wherein a=1, wherein X is methoxy, ethoxy, n-propoxy or isopropoxy, R 1 is methyl, ethyl, n-propyl or n-butyl, the second compound of formula (II) corresponds to SiX4, wherein X is alkoxy, in particular methoxy, ethoxy, n-propoxy or isopropoxy, and the third compound of formula (III) corresponds to R 2 bSiX3, wherein b=1, wherein X is methoxy, ethoxy, n-propoxy or isopropoxy, R is methyl, ethyl, n-propyl or n-butyl, and Q is a glycidyl group or a glycidyloxy group.

[0049] Other silanes which do not fall into one of the formulae (I) to (III) are not a constituent of the composition according to the invention and are therefore excluded.

[0050] In one embodiment of the composition of the present invention, the silane mixture comprises: 5% to 25% by weight, preferably 10% to 20% by weight, of at least one silane of formula (I); 3% to 15% by weight, preferably 6% to 11% by weight, of at least one silane of formula (II); and 5% to 20% by weight, preferably 8% to 15% by weight, of at least one silane of formula (III).

[0051] In a preferred embodiment, the silane mixture comprises: 5% to 15% by weight, preferably 8% to 12% by weight, of at least one silane of formula (I); 3% to 10% by weight, preferably 4% to 7% by weight, of at least one silane of formula (II); and 10% to 20% by weight, preferably 13% to 17% by weight, of at least one silane of formula (III).

[0052] In another preferred embodiment, the silane mixture comprises: 15% to 25% by weight, preferably 18% to 22% by weight, of at least one silane of formula (I); 5% to 15% by weight, preferably 10% to 13% by weight, of at least one silane of formula (II); and 5% to 10% by weight, preferably 7% to 9% by weight, of at least one silane of formula (III).

[0053] In a further embodiment of the composition according to the invention, at least one phosphate is a monophosphate or a polyphosphate and is used as an ammonium salt or an organic salt. Preferably, halogen-free phosphates are used, such as, for example, ammonium polyphosphate. Preferably, a mixture consisting of phosphates and sulfates is used.

[0054] In one embodiment, the composition of the invention comprises at least one metal alkoxide, in particular a zirconium alkoxide, such as zirconium n-propoxide. Preferably, the amount of the metal alkoxide is 1% to 3% by weight, in particular 1% to 2% by weight. The alkoxide used serves as a condensation catalyst in order to have as high a degree of condensation as possible even at low temperatures.

[0055] In another embodiment, at least one glycol ether is included in the composition of the present invention. Glycol ether is added to the composition as a mixture of water and at least one glycol ether, especially added with a mixing ratio of 60 parts of water and 40 parts of glycol ether. Use dipropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, 1-methoxy-2-propanol, tripropylene glycol monobutyl ether, propylene glycol butyl ether, ethylene glycol monophenyl ether as glycol ether, preferably use dipropylene glycol monomethyl ether. Glycol ether is used as a non-flammable solvent, which is not only well suited to the water of flame retardants, but also suitable for the alcohol of silane. When using glycol ether, the step of alcohol produced when preparing flame retardants can be omitted, as further shown below.

[0056] In a preferred embodiment, the composition of the present invention comprises:

[0057] - at least one phosphate and / or sulfate,

[0058] -According to R 1 SiX3 or R 1 At least one compound of the general formula (I) of 2SiX2, wherein R 1 As C1-C10 alkyl groups, methyl, ethyl, propyl, pentyl, hexyl, heptyl, octyl are preferred, and where X is alkoxy, in particular methoxy, ethoxy, n-propoxy or isopropoxy;

[0059] - at least one compound of the general formula (II) according to SiX4, wherein X is methoxy, ethoxy, n-propoxy or isopropoxy and butoxy;

[0060] -According to R 2 At least one compound of the general formula (III) of SiX3, wherein R 2 as methyl, ethyl, propyl, pentyl, hexyl, heptyl, octyl capable of being disconnected via -O- or -NH-, and functionalized as Q1 with an epoxy group or a vinyl group, and X as methoxy, ethoxy, n-propoxy, isopropoxy or butoxy; and

[0061] - at least one metal alkoxide, preferably a zirconium alkoxide,

[0062] - optionally at least one glycol ether, and

[0063] -water.

[0064] In another preferred embodiment, the composition of the present invention comprises:

[0065] - at least one phosphate and / or sulfate,

[0066] -According to R 1 SiX3 or R 1At least one compound of the general formula (I) of 2SiX2, wherein R 1 as methyl, ethyl, propyl, and wherein X is methoxy, ethoxy;

[0067] - at least one compound of the general formula (II) according to SiX4, wherein X is methoxy, ethoxy;

[0068] -According to R 2 At least one compound of the general formula (III) of SiX3, wherein R 2 as ethyl, propyl, pentyl capable of being disconnected via -O- or -NH-, and functionalized as Q1 with an epoxy group or a vinyl group, and X as methoxy, ethoxy; and

[0069] - at least one metal alkoxide, preferably a zirconium alkoxide,

[0070] - optionally at least one glycol ether, and

[0071] -water.

[0072] In another embodiment, the composition according to the invention can contain inorganic particles, in particular nanoparticles based on SiO2, such as silica gel or zeolites. The particles preferably used here have a size between 2 nm and 400 nm, preferably between 2 nm and 100 nm, particularly preferably between 2 nm and 50 nm. The amount of active substance absorbed can be further increased by adding inorganic particles.

[0073] The flame retardant of the present invention can be manufactured by a method comprising the following steps:

[0074] a) providing an aqueous suspension comprising at least one compound of formula (I), at least one compound of formula (II) and at least one compound of formula (III);

[0075] b) adding at least one catalyst, in particular a basic compound, to the suspension consisting of at least one compound of formula (I), formula (II) and formula (III);

[0076] c) heating a mixture consisting of at least one compound of formula (I), formula (II) and formula (III) and at least one catalyst;

[0077] d) adding at least one metal alkoxide, in particular a zirconium alkoxide, to the mixture, and

[0078] e1) separating the alcoholic phase formed from the aqueous phase of the mixture of at least one compound of formula (I), formula (II) and formula (III) (for example by evaporation), or

[0079] e2) adding a mixture of water and at least one glycol ether, and

[0080] f) adding at least one phosphate and / or sulfate to the mixture obtained in step e1) or step e2).

[0081] Basic compounds, such as alkali solutions, for example NaOH, KOH or ammonium hydroxide solutions are suitable as catalysts. Preferably, sodium hydroxide solution, in particular 0.1 molar sodium hydroxide solution, is used.

[0082] In one variant, in step f), 20% to 40% by weight, preferably 25% to 35% by weight, particularly preferably 30% by weight, of the mixture obtained in step e1) or step e2) is added to an aqueous phosphate solution, in particular a phosphate solution having a solids content of 50% by weight. The amount of the silane mixture in the finished composition is preferably 2% to 10% by weight, preferably 3% to 8% by weight, particularly preferably 4% to 6% by weight, for example 5% by weight.

[0083] The aqueous suspension of the flame retardant made from three silanes and phosphates and / or sulfates is stable and applied to the wood particles in the form of a spray. The application of the flame retardant is carried out during the manufacture of the wood-based panels.

[0084] Correspondingly, a method for manufacturing a wood-based panel is also provided, the method comprising the following steps:

[0085] - providing wood particles; in particular dry wood particles;

[0086] - sizing of the wood particles with a suitable adhesive,

[0087] - pressing the glued wood particles into artificial boards,

[0088] Therein, at least one of the above-described flame retardant compositions is applied, in particular sprayed, onto the wood particles before, during or after the application of the binder to the wood particles.

[0089] The amount of the flame retardant composition sprayed onto the wood particles is between 15% and 30% by weight, preferably between 20% and 25% by weight (based on solid bone dry wood).

[0090] Preferred adhesives are selected from the group consisting of formaldehyde adhesives, polyurethane adhesives, epoxy resin adhesives, and polyester adhesives, among which formaldehyde adhesives are mainly used.

[0091] In particular, phenolic resin adhesives (PF), cresol / resorcinol formaldehyde resin adhesives, urea-formaldehyde resin adhesives (UF) and / or melamine-formaldehyde resin adhesives (MF) can be used as formaldehyde adhesives.

[0092] As an alternative to formaldehyde adhesives, polyurethane adhesives based on aromatic polyisocyanates, in particular polydiphenyl diisocyanate (PMDI), toluene diisocyanate (TDI) and / or diphenylmethane diisocyanate (MDI), are suitable to a lesser extent, with PMDI being particularly preferred.

[0093] In one embodiment, in addition to the binder, paraffin wax (eg 3 wt % of 50 wt % paraffin wax emulsion) is also added to the wood particles to reduce water absorption and swelling. The paraffin wax emulsion is preferably sprayed onto the wood particles.

[0094] The manufactured wood-based panels can be open-stranded wood board (OSB), particle board or plywood.

[0095] Preferably, an OSB board is manufactured, wherein the method comprises the following steps:

[0096] a) manufacturing of wood chips from suitable wood (OSB chips),

[0097] b) optionally temporarily storing the wood chips, in particular in a silo or a bunker,

[0098] c) drying the wood shavings,

[0099] d) sorting or screening the wood chips according to their size,

[0100] e) sizing the wood chips with a suitable binder, in particular at least one isocyanate;

[0101] f) applying the glued wood chips to a conveyor belt by means of air screening and / or throw screening, and

[0102] g) Pressing the sized wood chips arranged on a conveyor belt.

[0103] Therein, at least one of the above-described flame retardant compositions is applied, in particular sprayed, onto the wood chips before, during or after the application of the binder to the wood chips.

[0104] As detailed above, strand board, also known as OSB (Oriented Strand Board), is produced from long wood chips (wood strands) in a multi-stage process.

[0105] In a first step, wood chips are removed from debarked round timber, preferably softwood, in the longitudinal direction by means of rotating knives.

[0106] The wood chips produced in this way can have a length of between 50 mm and 200 mm, preferably between 70 mm and 180 mm, particularly preferably between 90 mm and 150 mm; a width of between 5 mm and 50 mm, preferably between 10 mm and 30 mm, particularly preferably between 15 mm and 20 mm; and a thickness of between 0.1 mm and 2 mm, preferably between 0.3 mm and 1.5 mm, particularly preferably between 0.4 mm and 1 mm.

[0107] In one embodiment, the wood chips have, for example, a length of between 150 mm and 200 mm, a width of between 15 mm and 20 mm, a thickness of between 0.5 mm and 1 mm and a moisture content of maximum 50%.

[0108] OSB is typically made up of two cover layers delimiting a middle layer, wherein the cover layers and the middle layer can be made of different types of wood chips. Thus, planar chips can be used in the cover layers, while chips (or sawdust) of lower quality can be used in the middle layer. It is preferred that the chips for the cover layers are impregnated, for example sprayed, with the flame retardant according to the invention.

[0109] Isocyanates are preferably used as adhesives for OSB. In one embodiment, at least one isocyanate is based on aromatic polyisocyanates, in particular polydiphenyl diisocyanate (PMDI), toluene diisocyanate (TDI) and / or diphenylmethane diisocyanate (MDI), wherein PMDI is particularly preferred. However, melamine-urea-formaldehyde glue or phenolic glue can also be used. The melamine-urea-formaldehyde glue or phenolic glue also has high water resistance like PMDI. In addition, melamine is also used as a flame retardant.

[0110] As already mentioned, the at least one flame retardant can be applied, in particular sprayed, onto the wood chips in a size drum (coil) or in a trough mixer together with the addition of a binder.

[0111] A glue application device in the form of a web for the method according to the invention consists of a cartridge and at least one supply beam for conveying adhesive and compressed air by means of an atomizing disk, for driving which a pneumatic drive motor arranged in a housing is provided. Such a glue application device is described in DE 10 2008 046637 A1.

[0112] Suitable tank mixers are sold, for example, by the company Dieffenbacher. Such glue mixers ensure uniform glue distribution through their large chamber volume and optimal residence time of the material. In order to ensure an optimal glue application result, a constant liquid level in the mixer is maintained by means of a discharge valve.

[0113] The flame retardant composition may be used in both the cover layers and the intermediate layers of the OSB, or may also be used only in the cover layers of the OSB or only in the intermediate layers of the OSB.

[0114] After the adhesive with the flame retardant is applied to the wood chips, the sized wood chips are placed or spread on a conveyor belt and then pressed into OSB wood-based panels.

[0115] Pressing can be carried out at a pressing temperature between 150° C. and 250° C., preferably between 180° C. and 220° C., and at a pressing time between 30 sec and 240 sec, preferably between 100 sec and 210 sec, in particular between 150 sec and 180 sec.

[0116] The OSB produced by means of the method of the present invention therefore has a binder and the above-described flame retardant composition.

[0117] It was found that when a silane mixture was used as a fixing agent, the flame retardant content on the wood chips in the OSB after spreading and pressing was increased by up to 70% compared to samples without fixing agent.

[0118] The rough particle board (OSB) produced by the method described has a strength of more than 0.3 N / mm 2 , preferably greater than 0.4N / mm 2 , preferably greater than 0.45N / mm 2 , especially preferably greater than 0.5N / mm 2 The transverse tensile strength can be 0.3N / mm 2 and 0.6N / mm 2 In the range between 0.4 N / mm 2 and 0.6N / mm 2 In the range between 0.45 N / mm 2 and 0.55N / mm 2 in the range between.

[0119] Furthermore, the raw strand board (OSB) produced by the described method has a modulus of elasticity in the longitudinal direction of between 3200 MPa and 4000 MPa, preferably between 3400 MPa and 3800 MPa, and a modulus of elasticity in the transverse direction of between 1400 MPa and 1800 MPa, preferably between 1500 MPa and 1600 MPa.

[0120] The OSB artificial board of the present invention can have a strength of 300kg / m 3 and 1000kg / m 3 Between, preferably 500kg / m 3and 800kg / m 3 between 600kg / m 3 and 700kg / m 3 The packing density between.

[0121] The thickness of the OSB wood-based panel of the invention can be between 5 mm and 50 mm, preferably between 8 mm and 40 mm, with a thickness between 8 mm and 30 mm being particularly preferred.

[0122] As already mentioned above, however, it is also possible to produce particle boards using the method according to the invention.

[0123] Correspondingly, a method for manufacturing a particle board is provided, the method comprising the following steps:

[0124] a) producing wood chips from suitable wood,

[0125] b) crushing the wood chips by cutting to obtain wood dust;

[0126] c) sizing the wood chips with at least one binder;

[0127] d) applying the sized wood chips to a conveyor belt to form a multi-layer wood chip cake; and

[0128] e) Pressing the sawdust cake into wood-based panels.

[0129] Therein, at least one of the above-described flame retardant compositions is applied, in particular sprayed, onto the wood chips before, during or after the application of the binder to the wood chips.

[0130] The wood chips produced in the cutting process are divided into fine and coarse wood chip materials, wherein the larger wood chips are preferably used in the middle layer of the particle board, and the smaller wood chips are preferably used in the cover layer. It is preferred that the wood chips for the cover layer are infiltrated with the flame retardant of the present invention, for example sprayed.

[0131] In the case of particleboard, preferably formaldehyde-based adhesives are used, wherein for the middle layer, an amount of adhesive between 5% by weight and 8% by weight, preferably between 6% by weight and 7% by weight, is used, and for the cover layer, an amount of adhesive between 6% by weight and 10% by weight, preferably between 8% by weight and 9% by weight, is used. When using polyurethane-based adhesives such as PMDI in particleboard, the amount of adhesive in the middle layer is between 2% by weight and 5% by weight, preferably 3% by weight, and the amount of adhesive in the cover layer is between 4% by weight and 8% by weight, preferably 5% by weight.

[0132] After the glue is applied, the glued wood chips are spread onto a conveyor belt to form a wood chip cake. In the case of wood chips, it is usually done by means of air blowing, wherein first a first covering layer is spread, then an intermediate layer, and finally a second covering layer is spread.

[0133] Subsequently, the wood chip cake is first pre-compacted and then hot pressed at a temperature between 100° C. and 250° C., preferably between 130° C. and 220° C., in particular 200° C.

[0134] The wood-based panel of the invention in the form of a particle board can have a 3 and 1200kg / m 3 Between, preferably 500kg / m 3 and 1000kg / m 3 between 600kg / m 3 and 800kg / m 3 The packing density between.

[0135] The thickness of the wood-based panel according to the invention as a particle board can be between 3 mm and 20 mm, preferably between 5 mm and 15 mm, a thickness of 10 mm being particularly preferred.

[0136] The particle board according to the invention consists of 60% to 90% by weight, preferably 70% to 80% by weight, of wood chips and 5% to 20% by weight, preferably 10% to 15% by weight, of a binder. DETAILED DESCRIPTION

[0137] The present invention is explained in detail below based on a number of embodiments.

[0138] Embodiment 1:

[0139] 5 wt% dur GW80-ND (30% by weight) was admixed with a phosphate / polyphosphate-based flame retardant (solids content: approx. 50% by weight).

[0140] additive Synthesis of dur GW80-ND:

[0141] 15.23 g of glycidyloxypropyltriethoxysilane, 9.75 g of methyltriethoxysilane and 5.7 g of tetraethoxysilane were hydrolyzed with 1.67 g of 0.1 molar sodium hydroxide solution.

[0142] After a stirring time of 60 minutes at 40° C. under reflux, 2.04 g of zirconium n-propoxide (70% in isopropanol) were added. After a further stirring time of 60 minutes at room temperature, 8.22 g of water were added dropwise, and 7.1 g of ethanol were removed by means of a rotary evaporator (T=55° C., and p min =105mbar).

[0143] More cost-effective synthesis: Due to price pressure, on the one hand, the work step of solvent exchange by rotary evaporation should be avoided and on the other hand, more cost-effective silane mixtures should be used. To this end, the synthesis is adjusted:

[0144] Example 2: OSB is not flammable

[0145] 5 wt% dur GW80-N-D5 (30% by weight) was admixed with a phosphate / polyphosphate-based flame retardant (solids content: approx. 50% by weight).

[0146] additive Synthesis of dur GW80-N-D5:

[0147] 7.61 g of glycidyloxypropyltriethoxysilane, 19.5 g of methyltriethoxysilane and 11.4 g of tetraethoxysilane were hydrolyzed with 1.92 g of 0.1 molar sodium hydroxide solution. After a stirring time of 60 minutes at 40° C. under reflux, 1.24 g of zirconium n-propoxide (70% in isopropanol) were added.

[0148] After a further stirring time of 60 minutes at room temperature, 15.78 g of a mixture of 60 parts of water and 40 parts of dipropylene glycol methyl ether were added dropwise, and stirring was continued at room temperature for a further 30 minutes.

[0149] The finished additive now has a flash point of approximately 60° C. Addition of 25% by weight to the aqueous flame retardant (phosphate / polyphosphate) also results in a flash point of well above 70° C., so that it can be used without solvent exchange.

[0150] Then, the mixture is sprayed on the covering layer wood chips for OSB with 24 % by weight amount (by solid bone dry wood) in coil (gluing roller). Also put in 5 % by weight (100%) PMDI and 3 % by weight (50 % by weight) paraffin emulsion. For the middle layer, in another coil, 3.5 % by weight (100%) PMID and 3 % by weight (50 % by weight) paraffin emulsion spray wood chips. After spreading wood chips, extract wood chips from the covering layer and analyze the flame retardant content. Draw a value of 21 % by weight. In the zero sample without fixing agent, only 15 % by weight is found. The structure moves through a flat press (Contipressen) and is pressed into OSB (22mm) under pressure and temperature. Pull down the board sample after pressing and determine the flame retardant content equally. Draw a value of 20 % by weight for the sample with fixing agent there, and draw a value of 10 % by weight for the sample without fixing agent.

[0151] Example 3: Wood chip board is not flammable

[0152] 5 wt% dur GW80-N-D5 (30% by weight) was admixed with a phosphate / polyphosphate-based flame retardant (solids content: about 50% by weight) (prepared as in Example 2).

[0153] The mixture is then sprayed in a mixer in an amount of 20% by weight (based on solid bone dry wood) onto the covering wood chips for the wood chip board. 15% by weight of solid urea-formaldehyde glue (as a 60% solution) and 2% by weight of hot alkane are also added. The glue contains 5% by weight fl. / fl. of an ammonium salt-based curing agent (50% solution).

[0154] After spreading the top layer and the middle layer (gluing: 7% by weight of urea-formaldehyde glue (based on solid bone dry wood, with a 60% solution of a curing agent based on ammonium salt (5% by weight fl. / fl. on glue)). 2% by weight of hot alkane was also added to the middle layer sawdust. The gluing was also carried out in a tank mixer as in the top layer.

[0155] After spreading the cover layer and the intermediate layer, the wood chips were extracted from the cover layer and analyzed for the flame retardant content. A value of 16% by weight was obtained. In the zero sample without fixing agent, only 13% by weight was found. The wood chips were pressed into three-layer wood chip boards (18 mm) in a flat press. After pressing, the board samples were pulled off and the flame retardant content was also determined. There, a value of 15% by weight was obtained for the sample with the cover layer of fixing agent, while a value of 12% by weight was obtained for the sample without fixing agent.

Claims

1. A method for producing a wood-based panel from wood particles, wherein during the production process at least one flame retardant in the form of a suspension is applied to the wood particles, wherein the flame retardant suspension comprises: - at least one phosphate and / or sulfate, - A mixture consisting of: - at least one compound of formula (I) R 1 a SiX (4-a) (I), in -X is an alkoxy group, and -R 1 is an organic residue selected from: alkyl, cycloalkyl or phenyl, and - a = 1, 2, 3, especially 1 or 2, - at least one compound of formula (II) SiX4(II), wherein X is an alkoxy group, and - at least one compound of formula (III) R 2 SiX3(III), in -X is an alkoxy group, and -R 2 is an organic residue selected from: a C1-C10 alkyl group, wherein the C1-C10 alkyl group can be disconnected by -O- or -NH-, and -R 2 The present invention has at least one functional group Q1, wherein the functional group Q1 is selected from the group consisting of a methacrylic acid group, a methacryloyloxy group, a vinyl group and an epoxy group.

2. The method according to claim 1, It is characterized in that X is selected from C 1-6 - alkoxy, especially methoxy, ethoxy, n-propoxy, isopropoxy and butoxy.

3. The method according to any one of the preceding claims, It is characterized in that The compound of the general formula (I) has R 1 It is selected from C1-C10 alkyl, preferably C1-C8 alkyl, and particularly preferably methyl, ethyl, propyl, pentyl, hexyl, heptyl, and octyl.

4. The method according to any one of the preceding claims, It is characterized in that The compound of general formula (I) is R 1 SiX3 or R 1 2SiX2, where R 1 As C1-C10-alkyl radicals, preference is given to methyl, ethyl, propyl, pentyl, hexyl, heptyl, octyl, and in which X is alkoxy, in particular methoxy, ethoxy, n-propoxy or isopropoxy.

5. The method according to any one of the preceding claims, It is characterized in that The compound of the general formula (III) has R 2 Selected from: methyl, ethyl, propyl, pentyl, hexyl, heptyl, octyl which can be cleaved by -O- or -NH-.

6. The method according to any one of the preceding claims, It is characterized in that At least one functional group Q of the compound of formula (III) 1 Selected from: epoxy group, amino group and vinyl group.

7. The method according to any one of the preceding claims, It is characterized in that The silane mixture comprises: 5% to 25% by weight, preferably 10% to 20% by weight, of at least one silane of the formula (I); 3% to 15% by weight, preferably 6% to 11% by weight, of at least one silane of the formula (II); and 5% to 20% by weight, preferably 8% to 15% by weight, of at least one silane of the formula (III).

8. The method according to any one of the preceding claims, It is characterized in that The at least one phosphate is a monophosphate or a polyphosphate, or a mixture with a sulfate.

9. The method according to any one of the preceding claims, It is characterized in that The present invention comprises at least one glycol ether, in particular dipropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, 1-methoxy-2-propanol, tripropylene glycol monobutyl ether, propylene glycol butyl ether, and ethylene glycol monophenyl ether.

10. The method according to any one of the preceding claims, It is characterized in that At least one metal alkoxide is present, especially a zirconium alkoxide, for example zirconium n-propoxide.

11. The method according to any one of the preceding claims, It is characterized in that The at least one wood-based panel is a particle board (OSB), a chip board or a plywood.

12. The method according to any one of the preceding claims, It is characterized in that The following steps are provided: - providing wood particles; in particular dry wood particles; - gluing the wood particles with a suitable adhesive, - pressing the glued wood particles into artificial boards, It is characterized in that The at least one flame retardant is applied, in particular sprayed, onto the wood particles before, during or after the adhesive is applied to the wood particles.

13. An OSB board capable of being produced in a method according to any one of claims 1 to 12.

14. A particle board which can be produced by a method according to any one of claims 1 to 12.

15. A method for producing a flame retardant according to any one of claims 1 to 12, the method comprising the steps of: a) providing an aqueous suspension, the aqueous suspension comprising a mixture of at least one compound of the general formula (I), at least one compound of the general formula (II) and at least one compound of the general formula (III); b) adding at least one catalyst, in particular a basic compound, to the suspension consisting of the at least one compound of formula (I), the at least one compound of formula (II) and the at least one compound of formula (III); c) heating a mixture consisting of the at least one compound of formula (I), the at least one compound of formula (II), the at least one compound of formula (III) and the at least one catalyst; d) adding at least one metal alkoxide, in particular a zirconium alkoxide, to the mixture, and e1) separating the alcoholic phase formed from the aqueous phase of the mixture consisting of the at least one compound of formula (I), the at least one compound of formula (II) and the at least one compound of formula (III) (for example by evaporation), or e2) adding a mixture of water and at least one glycol ether, and f) adding at least one phosphate to the mixture obtained in step e1) or step e2).

Citation Information

Patent Citations

  • Gluing device for strands to manufacture oriented strand board plate, has supply bars feeding glue and compressed-air with spray disks, and spray disks driven by pneumatic drive motors, which are arranged in housing

    DE102008046637A1